Naming of short words is (almost) the same as naming of alphanumeric symbols: Evidence from two orthographies. - van den Boer, Madelon; Georgiou, George K.; de Jong, Peter F. (Journal of Experimental Child Psychology, 2016)
Throughout reading development, a gradual shift is seen in the processes underlying word identification from serial decoding toward parallel processing or sight word reading. It has been argued that this shift can be detected in the correlations between serial and discrete naming of alphanumeric symbols (digits and letters) and words. In the current study, we examined the relations between alphanumeric symbol naming and reading of monosyllabic and multisyllabic words and nonwords in two languages that differ in orthographic consistency: English and Dutch. A sample of 92 English-speaking Canadian children and 101 Dutch children, all in Grade 5, were assessed on discrete and serial naming of digits and letters and on serial and discrete naming of monosyllabic and multisyllabic words and nonwords. Results showed that discrete naming of alphanumeric symbols closely resembled discrete reading of monosyllabic words, suggesting that these words are processed in parallel in both languages. Both serial and parallel reading processes were found to underlie identification of multisyllabic words as well as monosyllabic nonwords. However, differences between the two languages emerged when processing multisyllabic nonwords. Whereas English-speaking children relied more on parallel reading processes to read multisyllabic nonwords, Dutch-speaking children processed these items serially. Theoretical implications of these findings are discussed.